Caracterização de crianças e adolescentes com distrofia muscular de duchenne acompanhados em um hospital universitário de referência na Amazônia Oriental - SILVA, Karoline Santos da (2022)
Objective: The aim of this study is to describe the sociodemographic and clinical profile of patients with Duchenne Muscular Dystrophy (DMD) treated at the Child and Adolescent Health Care Unit (UASCA) of the University Hospital Bettina Ferro de Souza (HUBFS) in Belém , Pará, Brazil. Method: This is a quantitative-descriptive, retrospective study, where sociodemographic data such as gender, education, race, current age and place of origin were collected, and clinical data such as diagnosis, age during clinical diagnosis, place where it was diagnosed, age of first appointment at HUBFS, first signs and symptoms, age at first signs and symptoms, family history, heart disease and previous surgeries. Result: At the end of the research, 29 medical records were selected for analysis. The profile of the patients identified that most of these were considered as brown, and that the average age was 12 years, while the average age of the first signs and symptoms was 3 years, and the place where most patients were was diagnosed at the University Hospital Bettina Ferro de Souza (HUBFS), and this diagnosis occurred on average at 8 years of age. Conclusion: There was a long delay for the diagnosis of DMD, this delay can lead the patient to lose their physical autonomy earlier and there is a worsening in the prognosis. This delay in diagnosis can be explained by the lack of a reference center in the Amazon.